Systemism - Claudius Gräbner-Radkowitsch; Jakob Kapeller (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2024)
This entry discusses the concept of "systemism", elaborates how it implicitly underpinned most seminal works of evolutionary-institutional economics, and explains how future research would benefit from making the systemist nature of evolutionary economics more explicit. More precisely, the paper clarifies the ontological and epistemological claims associated with systemism, and describes how the explicit use of systemism can support a pluralist meta-paradigm in heterodox economics and political economy in general, and evolutionary-institutional economics research in particular.
Keywords: B15; B25; B52; B55; C69; 330; Evolution; Institutions; Ontology; Epistemology; Models; Multi-Level Theorising; Emergence; Complexity